ADS503 : Knowledge management / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (2023)
The course explores in a systematic manner the fundamentals of knowledge management (KM). It covers the emergence and foundation of KM, and examines its critical components i.e. K-identification, K-creation, K-expansion, and K-sharing. It also discusses the issues and challenges in implementing KM. Case studies of successful KM implementation will be used to envisage the conceptual framework of KM practiced in public and private organization.